Normal values of M mode echocardiographic measurements of more than 2000 healthy infants and children in central Europe. Issue 6 (1st June 2000) - Kampmann, C; Wiethoff, C M; Wenzel, A; Stolz, G; Betancor, M; Wippermann, C-F; Huth, R-G; Habermehl, P; Knuf, M; Emschermann, T; Stopfkuchen, H
Abstract : OBJECTIVE: To obtain normal M mode (one dimensional) echocardiographic values in a substantial sample of normal infants and children. DESIGN: Data were obtained over three years from a single centre in central Europe. PATIENTS: 2036 healthy infants and children aged one day to 18 years. METHODS: In line with recommendations for standardising measurements from M mode echocardiograms, and using digital echocardiographic equipment, measurements were obtained of the following: right ventricular anterior wall thickness at end diastole, right ventricular end diastolic dimension, thickness of interventricular septum at end diastole and end systole, thickness of posterior wall of the left ventricle at end diastole and end systole, left ventricular dimension at end diastole and end systole, pulmonary and aortic valve diameter, and left atrial dimension. RESULTS: Measurements are presented graphically on centile charts with respect to body surface area, and as tables with mean and 2 SD values for newborns in relation to body weight, and for infants and children in relation to body surface area. Best fitting regression equations are given for each measured variable, using the 50th centile values. CONCLUSION: In comparison with previously published normal values, the presented charts and tables make it possible to judge echocardiographic measurements of a particular patient as normal or abnormal.